A mutant of Escherichia coli with an altered elongation factor Tu. - Pedersen, S (1976)
A previously isolated mutant of E. coli K12 HAK 88 [Kuwano, M., Endo, h & yamamoto, M. (1972) J. Bacteriol, 112, 1150-1156], contains a new protein that in two-dimensional gel electropherorgrams has the same molecular weight as normal elongation factor Tu, but whose isoelectric point is altered approximately 0.1 pH unit in the acidic direction. Peptide mapping, purification properties and the ratio of leucyl plus isoleucyl to methionyl plus cysteinyl residues of the normal elongation factor Tu protein and the new protein show a close similarity between the two. The mutation causing the altered electrophoretic mobility is located between argH and rif (79 min on the E. coli genetic map). These biochemical and genetic data indicate that strain HAK 88 has a mutationally altered tufB gene.